(untitled) (Literasi Nusantara, 2025)
This study explores the role of communication interactions within the Ikatan Mahasiswa Sumatera Utara (IKAMASU) regional student organization in alleviating homesickness among first-year migrant students at Universitas Trunojoyo Madura. Using a qualitative phenomenological approach, data were collected from purposively selected first-year North Sumatran students and organizational administrators through semi-structured interviews, participant observation, and documentation; data were analyzed following a Moustakas-inspired phenomenological procedure with method triangulation to ensure credibility. Findings show that IKAMASU functions as a family-like social space where intensive verbal exchanges (often in regional language), supportive nonverbal behaviors (open posture, empathic gestures), senior-member mentoring, and continuous digital communication together create emotional security and a sense of belonging. These communication processes reduce loneliness, normalize homesickness as a shared experience, and facilitate students’ psychological and social adaptation to campus life. The study concludes that structured, identity-based peer interaction within regional student organizations constitutes an effective social-support mechanism for mitigating homesickness and improving early university adjustment; universities should recognize and strengthen such community networks as part of student well-being initiatives.